Routing Protocols’ Behavior In Manet Networks (Mobile Ad Hoc Network) - Othman, Fouad Ziad; Khaled, Ali Mohamad (Ingeniería Solidaria, 2011)
The mobile Ad-Hoc networks or multiple jump networks are formed by radio links between nodes, without the need of central administration. In addition of working as final terminal, every node performs functions of bundles’ retransmission (routers) to extend communication up to destinations that are out of the coverage area. To achieve such goals, it requires a routing protocol that allows creating routes towards the destinations expected; these allow such network to be auto-configured and auto-organized eliminating the need of a predefined network infrastructure. Principally two types of protocols have been developed: reactive and proactive. In this article we study through simulation of discreet events using the networks simulatorns-2,to evaluate the behavior of different routing protocols, relative to the throughput, delivery and loss of bundles.
Keywords: manet; routing; Ad Hoc; simulation; ns -2